Enabling future nanomanufacturing through block copolymer self-assembly: A review. (December 2020) - Cummins, Cian; Lundy, Ross; Walsh, James J.; Ponsinet, Virginie; Fleury, Guillaume; Morris, Michael A.
Graphical abstract: Highlights: Introduction covers criteria of nanomanufacturing and concepts of block copolymers in thin film and solution state. Next, state-of-the-art in block copolymer thin film and solution processing is described. Overview of key contribution of block copolymers in energy, environmental, photonic, and biological applications. Outlook for impact and influence of block copolymers in nanomanufacturing including areas such as catalysis, membranes, metasurfaces and drug delivery nanodevices. Abstract: Self-assembly approaches, e.g. colloidal, emulsion and polymer phase separation, provide scientists with an exotic yet direct platform to access technologically desired nanostructures at competitive costs. In particular, soft nanomaterial systems such as block copolymer (BCP) materials present a powerful means to tailor templates and spatially controlled systems that are amenable to large scale manufacturing practices. BCP nanoarchitectures in bulk, solution and thin film form can act as structural motifs to template foreign materials and pave the way towards important applications across industry and society. While extensive literature and research efforts exist on electronic device uses using BCPs, we look at nascent applications outside the integrated circuit realm. Recent reports are discussed including for example; light-harvesting (energy – section 2), metasurfaces (photonics – section 3), nanofiltration membranes (environmental – section 4) and antibacterial activity (biological – section 5). We endeavour to illustrate the window of opportunity presented through BCP self-assembly for nanomanufacturing. We believe the highlights discussed will aid in directing new research initiatives and facilitate the large-scale integration of BCP materials with broad societal impact.